Deferoxamine Mitigates Radiation-Induced Tissue Injury in a Rat Irradiated TRAM Flap Model. Issue 1 (January 2015) - Mericli, Alexander F.; Das, Anusuya; Best, Ryan; Rodeheaver, Pamela; Rodeheaver, George; Lin, Kant Y.
<x xml:space="preserve">Abstract</x> Background: Radiation therapy results in permanent damage to the microvasculature, leading to dermal damage and inelasticity in normal tissues. Deferoxamine is a U.S. Food and Drug Administration–approved iron-chelating medication that has also been shown to increase angiogenesis. The authors hypothesize that the application of deferoxamine will result in increased vascularity and improved tissue elasticity in a rat irradiated transverse rectus abdominis musculocutaneous flap model. Methods: Fifteen rats underwent a transverse rectus abdominis myocutaneous flap and were randomized to three groups: control, radiation therapy, and radiation therapy plus deferoxamine. The flaps in the radiation therapy and radiation therapy plus deferoxamine groups were irradiated with 35 Gy in a single dose. Four weeks after irradiation, rats in the radiation therapy plus deferoxamine group were treated with deferoxamine. Flaps were imaged with micro–computed tomographic angiography. Flap creep and stress relaxation were assessed using a tensiometer. Hematoxylin and eosin, picrosirius red, and Verhoeff-van Gieson staining was performed. Results: Irradiated flaps demonstrated gross stigmata of cutaneous radiation injury within 4 weeks. Histologically, the epidermis in the radiation therapy flaps was found to be thicker than in the radiation therapy plus deferoxamine and control flaps (p < 0.001). Micro–computed tomographic angiography demonstrated a statistically significant (p < 0.05) increase in vascularity in the radiation therapy plus deferoxamine flaps compared with radiation therapy alone. The creep curve was indicative of increased elasticity in the radiation therapy plus deferoxamine flaps compared with radiation therapy flaps. Conclusion: Deferoxamine appears to mitigate radiation-induced hypovascularity and improve tissue elasticity in a rat model of soft-tissue reconstruction.